PENGARUH MODERNISASI SISTEM ADMINISTRASI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI USAHAWAN DI ITC CEMPAKA MAS JAKARTA - Andri Andri; Amelia Sandra (Jurnal Bina Akuntansi, 2017)
Tax is one of the largest nation’s country. To achieve the target of state revenue from the taxation sector, the Directorate General of Taxation takes steps in the framework of sustainable tax reform including tax reform reform in the field of policy and reform in the field of tax administration. So the tax reform creates a healthy and competitive tax system in encouraging Taxpayers to fulfill the rights and obligations of taxation. This study discusses the influence of modernization of tax administration system on taxpayer compliance of entrepreneurs in itc cempaka mas jakarta. Sampling technique used is non probability sampling with purposive sampling method and obtained data of 100 respondents from taxpayers compliance of entrepreneur in itc cempaka mas jakarta. Data analysis techniques and hypothesis testing to check each variable is done by descriptive statistical test, pooling test, classical assumption test, multiple regression analysis test, F test and t test using program SPSS 23. Based on the tests that have been done, it can be concluded that the modernization of tax administration system has an influence on the compliance of individual taxpayers.